Evaluation method for anti-glare and anti-reflection films

The anti-glare anti-reflection film with a controlled convexity density and layered structure addresses glare and reflection issues in high-definition displays, providing superior performance and quality assurance.

JP7603986B2Active Publication Date: 2024-12-23HIGASHIYAMA FILM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021097745
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2024-12-23
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

Existing anti-glare anti-reflection films struggle to provide effective glare suppression and anti-reflection performance, especially when applied to high-definition image display devices, and lack a reliable evaluation method for quality assessment.

Method used

The anti-glare anti-reflection film comprises a base film with a specific anti-glare layer and low refractive index layer, featuring a controlled density of surface convexities determined by Fourier transform analysis, along with a protective and adhesive layer for enhanced performance and evaluation.

Benefits of technology

The film effectively suppresses glare and exhibits excellent anti-reflection properties on high-definition displays, ensuring clear visibility and reduced reflectance, while the evaluation method ensures consistent quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603986000002
    Figure 0007603986000002
  • Figure 0007603986000003
    Figure 0007603986000003
  • Figure 0007603986000004
    Figure 0007603986000004
Patent Text Reader

Abstract

To provide an antiglare antireflection film in which glare is suppressed even in a case of being applied to a high-definition image display device, which exhibits the excellent antiglare property and exhibits the excellent antireflection performance, an evaluation method which can discriminate the antiglare antireflection film and a manufacturing method which can manufacture the antiglare antireflection film.SOLUTION: There is provided an antiglare antireflection film 10 in which an antiglare layer 16 and a low refractive index layer 14 are formed in this order on a base film 12, and the extraction protrusion density on the surface of the low refractive index layer 14 is between 3 / mm and 30 / mm. Here, the extraction protrusion density extracts a component with a wavelength between 14 μm and 50 μm from the wavelength distribution obtained with Fourier transformation of the irregularity distribution obtained by a laser microscope on any straight line, the difference of elevation with a recess that is adjacent in at least one direction indicates the number of protrusions being 0.1 μm or greater in the irregularity extraction distribution obtained with inverse Fourier transformation.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antiglare antireflection film, and an evaluation method and a manufacturing method thereof. More specifically, the present invention relates to an antiglare antireflection film used on the surface of an image display device provided as a touch panel or the like for electronic devices such as a liquid crystal image display device, an organic EL image display device, or a smartphone, and also relates to an evaluation method and a manufacturing method for such an antiglare antireflection film. [Background technology]

[0002] An anti-glare anti-reflection film may be disposed on the surface of an image display device provided as a touch panel of a liquid crystal image display device, an organic EL image display device, a car navigation system, a smartphone, etc., in order to prevent reflection of external light on the screen. In an image display device, anti-glare properties and anti-reflection properties are required from the viewpoint of reducing the influence of reflection of external light and making the display screen clearly visible. In particular, in an image display device intended for outdoor use, such as an image display device for an automobile or a smartphone, anti-glare properties and anti-reflection properties are required to make the display screen clearly visible even when exposed to strong external light such as sunlight. In recent years, image display devices have come to be used in meter cluster panels of automobiles, and image display devices are being mounted on various devices, including those used outdoors. In addition, with the increase in the resolution of image display devices, if a conventional anti-glare anti-reflection film is disposed on the surface of the image display device, glare occurs in which the luminance variation of the image is emphasized, and the image quality deteriorates, and it is required to suppress such glare. Under these circumstances, there is an increasing demand for improving the anti-glare and anti-reflection properties of image display devices.

[0003] A number of anti-glare and anti-reflection films have been proposed that can provide anti-glare and anti-reflection properties to image display devices. For example, Patent Document 1 discloses an anti-glare hard-coated film that prevents glare and improves the black density during black display by defining the arithmetic mean roughness Ra of the surface of the anti-glare hard-coated layer and the number of convex parts that exceed the roughness mean line, and also discloses an anti-glare hard-coated film that further provides an anti-reflection layer on the anti-glare layer. Patent Document 2 discloses an anti-glare and anti-reflection film that improves the black density and suppresses the haze value by defining parameters such as the ratio between the film thickness of the anti-glare hard-coated layer and the particle diameter of the organic fine particles contained in the anti-glare hard-coated layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-9007 A [Patent Document 2] JP 2010-78698 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is believed that known antiglare antireflection films, including those disclosed in Patent Documents 1 and 2, exhibit good antiglare and antireflection properties to a certain extent, but there is room for further improvement of antiglare and antireflection properties in antiglare antireflection films. For example, the antiglare antireflection film of Patent Document 1 has a certain range of the number of convex parts on the surface of the antiglare hard coat layer, but when applied to the surface of a high-definition image display device, there is still a possibility that glare will be strong. In addition, when an antireflection layer is further laminated on the surface of the antiglare hard coat layer, it is difficult to make the film thickness of the antireflection layer uniform, and good antireflection properties are not necessarily obtained. Patent Document 2 does not describe anything about the surface roughness of the antiglare antireflection film. In addition, the antiglare antireflection film of Patent Document 2 has a low haze value, so that incident light such as lighting is reflected while maintaining its outline, and antiglare properties may be insufficient.

[0006] The problem to be solved by the present invention is to provide an antiglare antireflection film that suppresses glare, exhibits good antiglare properties, and exhibits excellent antireflection performance even when applied to a high-definition image display device, as well as an evaluation method for identifying such an antiglare antireflection film, and a manufacturing method for manufacturing such an antiglare antireflection film. [Means for solving the problem]

[0007] In order to solve the above problems, the antiglare antireflection film of the present invention has an antiglare layer and a low refractive index layer formed in this order on a substrate film, and the extracted convexity density on the surface of the low refractive index layer is 3 / mm or more and 30 / mm or less. Here, the extracted convexity density refers to the number of convexities having a height difference of 0.1 μm or more with adjacent concaves in at least one direction in an extracted convexity / convexity distribution obtained by extracting components with wavelengths of 14 μm or more and 50 μm or less from a wavelength distribution obtained by Fourier transforming an unevenness distribution obtained by a laser microscope on an arbitrary straight line, and then performing an inverse Fourier transform.

[0008] Here, the density of the extracted convex portions on the surface of the antiglare layer may be 10 / mm or more and 38 / mm or less. The arithmetic mean roughness Ra of the surface of the low refractive index layer, as measured by a stylus surface roughness measuring device and specified in JIS B0601:2013, may be 0.015 μm or more and 0.06 μm or less. The arithmetic mean roughness Ra of the surface of the antiglare layer, as measured by a stylus surface roughness measuring device and specified in JIS B0601:2013, may be 0.015 μm or more and 0.06 μm or less.

[0009] The antiglare antireflection film may have a protective film on the surface of the low refractive index layer via an adhesive layer, and may have a transparent adhesive layer on the surface of the base film opposite to the low refractive index layer.

[0010] The method for evaluating an anti-glare anti-reflection film according to the present invention involves extracting components having wavelengths of 14 μm or more and 50 μm or less from a wavelength distribution obtained by Fourier transforming an unevenness distribution obtained on the surface of the anti-glare anti-reflection film with a laser microscope on any straight line, and then inverse Fourier transforming the extracted unevenness distribution obtained, and using the extracted convexity density, which is defined as the number of convexities having a height difference of 0.1 μm or more between itself and adjacent concaves in at least one direction, as an index to evaluate the quality of the anti-glare anti-reflection film.

[0011] Here, if the extracted convex portion density is 3 / mm or more and 30 / mm or less, the antiglare antireflection film may be evaluated as a non-defective product.

[0012] The method for producing an antiglare antireflection film according to the present invention comprises forming an antiglare layer on a substrate film such that the extracted convexity density on the surface is 10 / mm or more and 38 / mm or less, and forming a low refractive index layer by coating on the surface of the antiglare layer. Here, the extracted convexity density refers to the number of convexities having a height difference of 0.1 μm or more between adjacent concaves in at least one direction in an extracted convexity / convexity distribution obtained by extracting components having wavelengths of 14 μm or more and 50 μm or less from a wavelength distribution obtained by Fourier transforming an unevenness distribution obtained by a laser microscope on an arbitrary straight line, and then performing an inverse Fourier transform. Effect of the Invention

[0013] The anti-glare and anti-reflection film of the present invention has an extracted convexity density on the surface in the range of 3 / mm or more and 30 / mm or less, and therefore suppresses glare and has good anti-glare properties as well as excellent anti-reflection performance, even when applied to a high-definition image display device having a pixel density of, for example, 264 ppi (pixels per inch).

[0014] According to the evaluation method for antiglare antireflection films of the present invention, by using the density of extracted convex portions on the surface as an index for evaluation, it is possible to select antiglare antireflection films that suppress glare, have good antiglare properties, and have excellent antireflection performance even when applied to high-definition image display devices.

[0015] According to the method for producing an anti-glare anti-reflection film of the present invention, an anti-glare layer is formed and then a low refractive index layer is formed so that the density of extracted convex portions on the surface is in the range of 10 / mm or more and 38 / mm or less. This makes it possible to produce an anti-glare anti-reflection film that suppresses glare, has good anti-glare properties, and has excellent anti-reflection performance, even when applied to a high-definition image display device. [Brief description of the drawings]

[0016] [Figure 1] 1 is a cross-sectional view of an antiglare antireflection film according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of an antiglare antireflection film according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of an antiglare antireflection film according to a third embodiment of the present invention. [Figure 4] 1A shows a cross-sectional profile and FIG. 1B shows an extracted unevenness distribution obtained on the surface of the antiglare layer of the antiglare antireflection film according to Example 2 of the present invention. [Diagram 5] 1A shows a cross-sectional profile and FIG. 1B shows an extracted unevenness distribution obtained on the surface of a low refractive index layer of an antiglare antireflection film according to Example 2 of the present invention. [Figure 6] 1A shows a cross-sectional profile and FIG. 1B shows an extracted unevenness distribution obtained on the surface of the antiglare layer of the antiglare antireflection film according to Comparative Example 1 of the present invention. [Figure 7] 1A shows a cross-sectional profile and FIG. 1B shows an extracted unevenness distribution obtained on the surface of a low refractive index layer of an antiglare antireflection film according to Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in detail below.

[0018] [Antiglare and antireflection film according to the first embodiment] <Overall structure of anti-glare and anti-reflection film> Fig. 1 is a cross-sectional view of an antiglare antireflection film 10 according to a first embodiment of the present invention. As shown in Fig. 1, the antiglare antireflection film 10 according to the first embodiment of the present invention has a base film 12, a low refractive index layer 14 formed on the surface of the base film 12, and an antiglare layer 16 formed between the base film 12 and the low refractive index layer 14. In other words, the antiglare antireflection film 10 has the base film 12, the antiglare layer 16, and the low refractive index layer 14 in this order. The low refractive index layer 14 is exposed on the outermost surface of the antiglare antireflection film 10 as a whole.

[0019] (Extracted convexity density) As will be described in detail later, since the antiglare layer 16 contains the convex-forming particles 18, an uneven structure is formed on the surface of the antiglare antireflection film 10. The uneven structure on the surface of the antiglare antireflection film 10 has a significant effect on the antiglare properties and antireflection performance of the antiglare antireflection film 10.

[0020] The unevenness distribution (cross-sectional profile) on the surface of the anti-glare anti-reflection film 10 can be obtained by a laser microscope. In particular, it can be suitably obtained by a 3D laser measuring microscope. In the cross-sectional profile of the anti-glare anti-reflection film 10 according to this embodiment, when the distribution of the uneven structure is expressed in terms of wavelength, unevenness with a wavelength of 14 μm or more and 50 μm or less is included. Here, unevenness with a wavelength of 14 μm or more and 50 μm or less refers to unevenness with a wavelength of 14 to 50 μm, that is, a wave number of 0.2 to 0.7 μm, in a Fourier spectrum showing the contribution of each wavelength component obtained by Fourier transforming the cross-sectional profile. -1 The uneven structure that gives a distribution of wavelengths of 14 to 50 μm has a significant effect on the antiglare properties and antireflection performance of the antiglare reflective film 10.

[0021] Therefore, the distribution of the uneven structure in the antiglare antireflection film 10 according to the present embodiment is expressed by the extracted convex density. The extracted convex density refers to the number of convex parts having a height difference of 0.1 μm or more with adjacent concave parts in at least one direction (at least one of the left and right sides of the line) in the extracted uneven distribution obtained by extracting components with wavelengths of 14 μm or more and 50 μm or less from the wavelength distribution obtained by Fourier transforming the cross-sectional profile obtained by a laser microscope on an arbitrary straight line, and performing an inverse Fourier transform. In other words, when the convex parts with wavelengths of 14 to 50 μm are extracted with a bandpass filter at an arbitrary 1 mm point on the cross-sectional profile, the number of convex parts having a peak with a height difference of 0.1 μm or more with at least one adjacent concave part is defined as the extracted convex density. The length of the straight line on the cross-sectional profile for performing the Fourier transform is not particularly limited, and may be selected so as to include a sufficient number of convex parts for accurate analysis. For example, a straight line with a length of about 1 mm, such as 0.5 mm or more and 2 mm or less, may be set at an arbitrary point on the surface.

[0022] In the antiglare antireflection film 10 according to the present embodiment, the extracted convex density defined as above is in the range of 3 / mm or more and 30 / mm or less. The convex parts formed on the surface of the antiglare layer 16 diffuse reflected light, thereby enhancing the antiglare properties. If the extracted convex density is 3 / mm or more, good antiglare properties can be obtained. From the viewpoint of further enhancing these effects, the extracted convex density is more preferably 5 / mm or more, and even more preferably 6 / mm or more. On the other hand, the unevenness on the surface of the antiglare layer 16 can cause glare, but if the extracted convex density is suppressed to 30 / mm or less, the occurrence of glare is suppressed, a good low reflectance is obtained, and the antiglare antireflection film 10 has a good blackness in the black display part. From the viewpoint of further enhancing these effects, the extracted convex density is more preferably 25 / mm or less, and even more preferably 15 / mm or less. The extracted convex density of anti-glare anti-reflection film 10 is evaluated for the surface of low refractive index layer 14, that is, the surface of anti-glare anti-reflection film 10 as a whole. The extracted convex density on the surface of anti-glare anti-reflection film 10 can be controlled by the specific configurations of low refractive index layer 14 and anti-glare layer 16, such as the component compositions and thicknesses of low refractive index layer 14 and anti-glare layer 16, and in particular the particle size and density of convex-forming particles 18 in anti-glare layer 16.

[0023] In this embodiment, the unevenness distribution on the surface of the antiglare antireflection film 10 is determined using a laser microscope, rather than a surface roughness measuring device using a stylus, which is commonly used for measuring surface roughness, in order to evaluate the unevenness structure distributed on a small scale such as a wavelength of 14 to 50 μm with high spatial resolution. In addition, by using an evaluation method based on the reflection of light, the antiglare reflective film 10 can be evaluated with a high correlation with the antiglare property and antireflection property, which are phenomena that reflect the behavior of light reflection. For example, as shown in the examples below, when the low refractive index layer 14 is laminated on the antiglare layer 16, the attenuation of the unevenness (attenuation of the height difference of the unevenness and the distribution density of the unevenness) in the cross-sectional profile obtained by the laser microscope tends to be large, even though the change in the surface roughness measured by the surface roughness measuring device using a stylus is small. In particular, the attenuation of the unevenness at wavelengths of 14 to 50 μm tends to be large. It is speculated that these tendencies are due to the antireflection effect of the low refractive index layer 14, which reduces the reflectance of the laser light of the laser microscope. In other words, by using a laser microscope, it is possible to evaluate the optical properties of the surface of the antiglare and antireflection film 10, such as antiglare properties and antireflection properties, including the antireflection effect of the low refractive index layer 14.

[0024] In addition, in this embodiment, the wavelength on the cross-sectional profile for evaluating the extracted convexity density is set to a range of 14 μm or more and 50 μm or less for the following reason. Although the unevenness with a wavelength of 14 μm or more is highly effective in improving anti-glare properties due to the diffuse reflection of light, the resulting lens effect distorts the pixels of a high-definition image display device, increasing the luminance distribution, and making the observer feel that the image display device is glare. By evaluating it as the extracted convexity density, it can be used as an index of a film that suppresses glare and exhibits excellent anti-glare properties. Note that, for unevenness with a wavelength of less than 14 μm, it is considered that the light can be diffusely reflected well because the attenuation of the unevenness due to the formation of the low refractive index layer 14 is small, but since the measurement result of the laser microscope contains a lot of noise components, it is not included in the evaluation target from the viewpoint of increasing the accuracy of the evaluation of the extracted convexity density. On the other hand, by evaluating the unevenness with a wavelength of 50 μm or less as the extracted convexity density, the unevenness structure that contributes to improving the anti-reflection properties can be effectively evaluated. Asperities with wavelengths exceeding 50 μm are not evaluated because their contribution to antireflection properties is considered to be small, also because the attenuation of the asperities is small when the low refractive index layer 14 is laminated.

[0025] Here, the surface profile used to evaluate the density of extracted convex portions is extracted by filtering processing such as a bandpass filter as described above, and the surface profile includes unevenness that is only a part of a mountain. However, even if it is a part of a mountain, if the convex portion has a peak with a height difference of 0.1 μm or more with at least one adjacent concave portion, the convex portion acts as a lens and causes glare. Therefore, by controlling the number of convex portions on the surface of the antiglare antireflection film 10 that have a peak with a height difference of 0.1 μm or more with at least one adjacent concave portion at a wavelength of 14 to 50 μm, it is possible to obtain good antiglare and antireflection properties with reduced glare.

[0026] As described above, unevenness having a wavelength of more than 50 μm contributes little to the anti-reflection properties of the anti-glare anti-reflection film 10 and is not included in the evaluation of the density of extracted convexities. However, if it is present on the surface of the anti-glare anti-reflection film 10, it is effective in improving the anti-glare properties, but may affect the appearance quality of the display due to graininess. The number of convexities having a wavelength of more than 50 μm is evaluated as the number of convexities having a peak with a height difference of 0.1 μm or more with at least one adjacent concave portion when the unevenness having a wavelength of more than 50 μm is extracted with a low-pass filter at an arbitrary point 1 mm in a cross-sectional profile obtained by a laser microscope. From the viewpoint of improving the anti-glare properties, the number of convexities having a wavelength of more than 50 μm is preferably 5 pieces / mm or more, more preferably 8 pieces / mm or more, or 10 pieces / mm or more. On the other hand, from the viewpoint of maintaining the appearance quality of the display without making the display surface grainy, the number of convexities having a wavelength of more than 50 μm is preferably 33 pieces / mm or less, more preferably 30 pieces / mm or less, or 25 pieces / mm or less.

[0027] Based on the measurement results using a laser microscope, the arithmetic mean roughness Ra of the surface can be evaluated in addition to the extracted convex density. The antiglare antireflection film 10 according to the present embodiment preferably has the extracted convex density in the above range, and also has the arithmetic mean roughness Ra in the following range. Here, the arithmetic mean roughness Ra of the surface can be defined according to JIS B0601:2013 for the measurement results using a laser microscope (hereinafter the same applies). Specifically, the arithmetic mean roughness Ra of the surface of the antiglare antireflection film 10 is preferably 0.05 μm or more. If Ra is 0.05 μm or more, a large number of relatively uniform and fine irregularities are present on the surface of the low refractive index layer 14, and good antiglare properties can be obtained. Ra is more preferably 0.06 μm or more, and even more preferably 0.07 μm or more. On the other hand, the arithmetic mean roughness Ra of the surface of the antiglare antireflection film 10 is preferably 0.11 μm or less. If Ra is 0.11 μm or less, glare on the surface can be effectively suppressed. Ra is more preferably 0.10 μm or less, and further preferably 0.09 μm or less.

[0028] (Other characteristics) As described above, by evaluating the uneven structure on the surface of the antiglare antireflection film 10 using a laser microscope, the uneven structure reflected as the optical properties of the antiglare antireflection film 10 can be evaluated more accurately than when using a stylus-type surface roughness measuring device, but the evaluation using a stylus-type surface roughness measuring device can be performed more easily, and by using it in combination with the evaluation using a laser microscope, an antiglare antireflection film 10 with even better properties can be obtained. Specifically, if the arithmetic mean roughness Ra measured by a stylus-type surface roughness measuring device on the surface of the antiglare antireflection film 10 (the surface of the low refractive index layer 14) is 0.015 μm or more, further 0.018 μm or more, or 0.020 μm or more, the surface of the low refractive index layer 14 will have a large number of relatively uniform and fine unevenness, and good antiglare properties can be obtained. On the other hand, if the arithmetic mean roughness Ra is 0.06 μm or less, further 0.05 μm or less, or 0.04 μm or less, glare on the surface can be effectively suppressed. The arithmetic mean roughness Ra measured by a stylus surface roughness measuring instrument may be specified in accordance with JIS B0601:2013 (hereinafter the same applies). The reason why the preferred range of the arithmetic mean roughness Ra measured by a stylus surface roughness measuring instrument is in a region with smaller values ​​than the preferred range of the arithmetic mean roughness Ra based on the measurement results by the laser microscope is that the laser microscope has higher spatial resolution than the stylus surface roughness measuring instrument.

[0029] Furthermore, it is preferable that the antiglare antireflection film 10 has a luminous reflectance of 1.3% or less. This increases the blackness (black density) when the image background of the image display device is made black, improving the contrast of the image. From the viewpoint of further enhancing this effect, the luminous reflectance is more preferably 1.2% or less, and even more preferably 1.0% or less. The lower the luminous reflectance, the more preferable, and although there is no particular lower limit, it is usually 0.3% or more. The luminous reflectance may be measured with an integrating sphere for diffuse reflected light including specular reflected light (SCI: Specular Component Include).

[0030] The haze (Hz) of the antiglare antireflection film 10 is preferably 2.0% or more. This provides good antiglare properties. From the viewpoint of further enhancing the antiglare property improvement effect, the haze is more preferably 4.0% or more, and even more preferably 6.0% or more. On the other hand, the haze of the antiglare antireflection film 10 is preferably 20% or less. This allows the display screen to be clearly viewed even in a high-definition image display device. From the viewpoint of further enhancing the effect, the haze is more preferably 15% or less, and even more preferably 10% or less.

[0031] Each layer constituting the antiglare and antireflection film 10 will now be described in detail.

[0032] <Base film> The specific configuration of the base film 12 is not particularly limited as long as it has transparency. Examples of the base film 12 include a transparent polymer film and a glass film. The transparency means that the total light transmittance in the visible light wavelength region is 50% or more, and the total light transmittance is more preferably 85% or more. The total light transmittance can be measured in accordance with JIS K7361-1 (1997). The thickness of the base film 12 is not particularly limited, but is preferably in the range of 2 μm to 500 μm from the viewpoint of excellent handling. More preferably, it is 2 μm to 200 μm. Note that the term "film" generally refers to a film having a thickness of less than 0.25 mm, but even if the thickness is 0.25 mm or more, it is included in the "film" as long as it can be rolled into a roll.

[0033] When the base film 12 is a transparent polymer film, examples of the polymer material constituting the base film 12 include polyester resins such as polyethylene terephthalate resin and polyethylene naphthalate resin, polycarbonate resin, poly(meth)acrylate resin, polystyrene resin, polyamide resin, polyimide resin, polyacrylonitrile resin, polypropylene resin, polyethylene resin, polyolefin resins such as polycycloolefin resin and cycloolefin copolymer resin, polyphenylene sulfide resin, polyvinyl chloride resin, polyvinylidene chloride resin, and polyvinyl alcohol resin. The polymer material of the base film 12 may be composed of only one of these materials, or may be composed of a combination of two or more of them. Among these, polyethylene terephthalate resin, polyimide resin, polycarbonate resin, poly(meth)acrylate resin, polycycloolefin resin, and cycloolefin copolymer resin are more preferable from the viewpoint of optical properties and durability. Furthermore, in the case where an image display device including a polarizing plate is observed through polarized sunglasses, if the absorption axis of the polarized light of the image display device and the absorption axis of the polarized light of the polarized sunglasses are perpendicular to each other, the screen becomes dark and cannot be seen (blackout), and from the viewpoint of suppressing color unevenness (rainbow unevenness) due to the retardation of the base film 12, a film made of a highly optically isotropic polycycloolefin resin, cycloolefin copolymer resin, or polyethylene terephthalate resin having a retardation of 3000 nm or more is particularly preferred.

[0034] The base film 12 may be composed of a single layer containing one or more of the above-mentioned polymeric materials, or may be composed of two or more layers, such as a layer containing one or more of the above-mentioned polymeric materials and a layer containing one or more of a different polymeric material.

[0035] <Anti-glare layer> The antiglare layer 16 imparts antiglare properties to the antiglare antireflection film 10 and also contributes to improving scratch resistance. The specific configuration of the antiglare layer 16 is not limited as long as it can impart antiglare properties to the antiglare antireflection film 10 by forming irregularities on the surface of the antiglare antireflection film 10, but it is preferable for the antiglare layer 16 to contain a binder resin and particles (particles for forming convexities) 18 for forming convexities on the surface of the antiglare layer 16. Details of the configurations of the binder resin and the particles for forming convexities 18 will be described later.

[0036] The antiglare layer 16 preferably has a hardness of pencil hardness H or more. The pencil hardness can be measured in accordance with JIS K5600-5-4. The thickness of the antiglare layer 16 is preferably 0.5 μm or more from the viewpoint of having sufficient hardness. More preferably, it is 1.2 μm or more, and even more preferably, it is 3.0 μm or more. In addition, the thickness of the antiglare layer 16 is preferably 20 μm or less from the viewpoint of easily suppressing curling caused by the difference in thermal shrinkage with the base film 12. More preferably, it is 15 μm or less, even more preferably, it is 10 μm or less, and particularly preferably, it is 6.0 μm or less.

[0037] The antiglare layer 16 preferably has an extracted convex density of 10 or more on the surface. The definition of the extracted convex density on the layer surface is the same as that described above for the surface of the antiglare antireflection film 10 as a whole, that is, the surface of the low refractive index layer 14. If the extracted convex density is 10 / mm or more, good antiglare properties are easily obtained even when the low refractive index layer 14 is laminated. From the viewpoint of further enhancing this effect, the extracted convex density is preferably 15 / mm or more, more preferably 20 / mm or more. On the other hand, the extracted convex density on the surface of the antiglare layer 16 is preferably 38 / mm or less. If the extracted convex density is 38 / mm or less, glare is unlikely to occur even when the low refractive index layer 14 is laminated, and the antiglare antireflection film 10 has a good low reflectance and has a good blackness in the black display part. From the viewpoint of further enhancing this effect, the extracted convex density is preferably 37 / mm or less, more preferably 36 / mm or less.

[0038] In addition, the arithmetic mean roughness Ra of the surface of the antiglare layer 16 on which the surface irregularities are formed is preferably 0.07 μm or more based on the measurement results using a laser microscope. If this Ra is 0.07 μm or more, even if the low refractive index layer 14 is formed on the antiglare layer 16, a good antiglare property can be obtained due to the presence of a large number of relatively uniform and fine irregularities. Ra is more preferably 0.08 μm or more, and even more preferably 0.10 μm or more. On the other hand, the arithmetic mean roughness Ra of the surface of the antiglare layer 16 is preferably 0.15 μm or less. If this Ra is 0.15 μm or less, glare on the surface of the antiglare antireflection film 10 can be effectively suppressed. Ra is more preferably 0.13 μm or less, and even more preferably 0.12 μm or less.

[0039] As described above, the density of extracted convex portions on the surface of the anti-glare reflective film 10 as a whole is 3 / mm or more and 30 / mm or less. The preferred arithmetic mean roughness Ra based on the measurement results of a laser microscope is 0.05 μm or more and 0.11 μm or less on the surface of the anti-glare anti-reflection film 10 as a whole. In other words, the preferred number of extracted convex portions and the arithmetic mean roughness Ra listed here for the surface of the anti-glare layer 16 are all larger than the values ​​for the anti-glare anti-reflection film 10 as a whole. This is because the uneven structure is formed on the surface of the anti-glare layer 16 so that the density and height difference are sufficient to impart a predetermined extracted convex portion density to the surface of the anti-glare reflective film 10 as a whole, taking into account that the unevenness is attenuated when the low refractive index layer 14 is formed on the surface of the anti-glare layer 16. The attenuation of the unevenness due to the formation of the low refractive index layer 14 is presumably due to the fact that the presence of the low refractive index layer 14 actually reduces the distribution density and height difference of the unevenness structure on the surface, and also because the anti-reflection effect of the low refractive index layer 14 reduces the reflectance of the laser light of the laser microscope used to evaluate the extracted convexity density and the arithmetic mean roughness Ra.

[0040] Furthermore, the arithmetic mean roughness Ra of the surface of the antiglare layer 16 on which the surface irregularities are formed is preferably 0.015 μm or more, as measured by a stylus surface roughness measuring device. If this Ra is 0.015 μm or more, even if the low refractive index layer 14 is formed on the antiglare layer 16, a good antiglare property can be obtained due to the presence of a large number of relatively uniform and fine irregularities. From the viewpoint of further enhancing this effect, Ra is more preferably 0.020 μm or more, and even more preferably 0.025 μm or more. On the other hand, the arithmetic mean roughness Ra of the surface of the antiglare layer 16 is preferably 0.06 μm or less. If this Ra is 0.06 μm or less, glare on the surface of the antiglare antireflection film 10 can be effectively suppressed. Ra is more preferably 0.05 μm or less, and even more preferably 0.04 μm or less. The range of 0.015 μm or more and 0.06 μm or less given here as the preferred range of the arithmetic mean roughness Ra obtained with a stylus surface roughness measuring device for the surface of the antiglare layer 16 is the same as the range given above for the entire surface of the antiglare antireflection film 10, that is, the surface of the low refractive index layer 14. The reason for this is that, when evaluating surface irregularities with a stylus surface roughness measuring device, the spatial resolution is not so high as when a laser microscope is used, and the measurement results are not affected by light reflection by the low refractive index layer 14.

[0041] (binder resin) The specific type of binder resin constituting the antiglare layer 16 is not particularly limited, but from the viewpoint of the scratch resistance of the antiglare layer 16, a cured product of a thermosetting compound or a cured product of an ionizing radiation curable compound is preferable. From the viewpoint of productivity, a cured product of an ionizing radiation curable compound is more preferable. The ionizing radiation means an electromagnetic wave or a charged particle beam having an energy quantum capable of polymerizing or crosslinking molecules. Examples of the ionizing radiation include electromagnetic waves such as ultraviolet rays (UV), X-rays, and gamma rays, and charged particle beams such as electron beams (EB), alpha rays, and ion beams. Of these, ultraviolet rays (UV) are particularly preferable from the viewpoint of productivity.

[0042] Examples of the ionizing radiation curable resin include monomers, oligomers, prepolymers, etc. having a reactive group reactive to ionizing radiation. Examples of the reactive group reactive to ionizing radiation include radical polymerization type reactive groups having an ethylenically unsaturated bond, such as acryloyl group, methacryloyl group, allyl group, vinyl group, etc., and cationic polymerization type reactive groups, such as oxetanyl group. Among these, acryloyl group, methacryloyl group, and oxetanyl group are more preferable, and acryloyl group and methacryloyl group are particularly preferable. That is, as the ionizing radiation curable resin, (meth)acrylate is particularly preferable. In this specification, "(meth)acrylate" means "at least one of acrylate and methacrylate". "(meth)acryloyl" means "at least one of acryloyl and methacryloyl". "(meth)acrylic" means "at least one of acrylic and methacrylic".

[0043] Examples of (meth)acrylates constituting the ionizing radiation curable resin include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, and aryl (meth)acrylate. Among these, urethane (meth)acrylate is particularly preferred from the viewpoint of excellent flexibility. When the curable composition for forming the antiglare layer 16 contains urethane (meth)acrylate as the ionizing radiation curable resin, cracking of the base film 12 is easily suppressed even if the base film 12 is made of, for example, polycycloolefin or cycloolefin copolymer and is relatively prone to cracking.

[0044] The curable composition forming the antiglare layer 16 may or may not contain a non-ionizing radiation curable resin in addition to the ionizing radiation curable resin. The curable composition forming the antiglare layer 16 may also contain a photopolymerization initiator. If necessary, it may also contain additives that are generally added to curable compositions. Furthermore, if necessary, the curable composition may also contain small-diameter particles that are particles having a smaller particle diameter than the convex-forming particles 18.

[0045] Examples of the non-ionizing radiation curable resin used in combination with the ionizing radiation curable resin include thermoplastic resins and thermosetting resins. Examples of the thermoplastic resins include polyester resins, polyether resins, polyolefin resins, polyamide resins, etc. Examples of the thermosetting resins include unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc.

[0046] Examples of the photopolymerization initiator include alkylphenone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2'-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and the like. Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more. The content of the photopolymerization initiator is preferably 0.1% by mass or more, more preferably 1% by mass or more, based on the total solid content of the curable composition. On the other hand, the content is preferably 10% by mass or less, more preferably 5% by mass or less.

[0047] (Particles for forming convex portions) The convex-forming particles 18 are contained in the anti-glare layer 16 to form convex portions on the surface of the anti-glare layer 16. The convex portions formed on the surface of the anti-glare layer 16 by the convex-forming particles 18 allow the anti-glare layer 16 to diffuse reflected light and have good anti-glare properties.

[0048] The particles 18 for forming the convex portion may be inorganic particles or organic particles. Examples of the inorganic particles include metal oxide particles made of an oxide of a metal such as titanium, zirconium, silicon, aluminum, or calcium. These may be used alone as the inorganic particles, or two or more types may be used in combination. Examples of the organic particles include resin particles made of resins such as (meth)acrylic resin, styrene resin, styrene-(meth)acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenolic resin, polyethylene resin, and cellulose. These may be used alone as the organic particles, or two or more types may be used in combination. Among these, organic particles are preferred, and (meth)acrylic particles are particularly preferred from the viewpoint of excellent transparency. As the particles 18 for forming the convex portion, inorganic particles and organic particles may be used in combination.

[0049] The shape of the convex-forming particles 18 is not particularly limited, and may be spherical, needle-like, scaly, rod-like, fibrous, amorphous, etc. Of these, spherical is preferable. With regard to the particle size distribution, from the viewpoint of uniformly diffusing or scattering light in the antiglare layer 16 and on its surface, monodisperse particles with a uniform particle size are preferable.

[0050] From the viewpoint of efficiently diffusing reflected light, the average particle diameter of the convex portion forming particles 18 is preferably 1 μm or more. When the average particle diameter is 1 μm or more, the effect of diffusing reflected light is increased. From the viewpoint of further enhancing the effect, the average particle diameter is more preferably 2 μm or more, and even more preferably 3 μm or more. On the other hand, the average particle diameter of the convex portion forming particles 18 is preferably 20 μm or less. When the average particle diameter is 20 μm or less, the thickness of the antiglare layer 16 is not too thick, and the antiglare antireflection film 10 is less likely to curl due to the curing shrinkage of the film. In addition, when the antiglare antireflection film 10 is installed on a high-definition image display device, glare due to brightness variation is less likely to occur, and the display screen can be clearly viewed. From the viewpoint of further enhancing these effects, the average particle diameter of the convex portion forming particles 18 is more preferably 15 μm or less, and even more preferably 10 μm or less. Here, the average particle diameter of the convex-forming particles 18 can be a value calculated from the particle number distribution obtained by converting the distribution measured by the Coulter counter method into a particle number distribution. The Coulter counter method is a particle diameter measurement method that uses electrical resistance, and measures the average particle diameter by measuring the change in electrical resistance between two electrodes that occurs when particles pass through a sensitive region.

[0051] The ratio (t / d) of the thickness (t) of the antiglare layer 16 to the average particle diameter (d) of the particles for forming the convex portion is preferably 1.2 or more. If t / d is 1.2 or more, a good reflectance reducing effect can be obtained when the low refractive index layer 14 is laminated. From the viewpoint of further enhancing the effect, t / d is more preferably 1.3 or more, and even more preferably 1.4 or more. On the other hand, t / d is preferably 2.0 or less. If t / d is 2.0 or less, surface irregularities that can provide good antiglare properties are formed in the antiglare layer 16. From the viewpoint of further enhancing the effect, t / d is more preferably 1.8 or less, and even more preferably 1.6 or less.

[0052] (Additives) As described above, the curable composition constituting the antiglare layer 16 may contain additives, etc., as necessary. Examples of such additives include antifouling agents, dispersants, leveling agents, defoamers, thixotropic agents, antibacterial agents, flame retardants, slip agents, refractive index adjusters, adhesion improvers, etc. Furthermore, a solvent may be contained as necessary.

[0053] Examples of the solvent used in the curable composition forming the antiglare layer 16 include alcohol-based solvents such as ethanol, isopropyl alcohol (IPA), n-butyl alcohol (NBA), ethylene glycol monomethyl ether (EGM), ethylene glycol monoisopropyl ether (IPG), propylene glycol monomethyl ether (PGM), and diethylene glycol monobutyl ether, ketone-based solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, and acetone, aromatic solvents such as toluene and xylene, ester-based solvents such as ethyl acetate (EtAc), propyl acetate, isopropyl acetate, and butyl acetate (BuAc), and amide-based solvents such as N-methylpyrrolidone, acetamide, and dimethylformamide. These solvents may be used alone or in combination of two or more.

[0054] When a solvent is used, the solid content concentration of the curable composition (concentration of components other than the solvent) may be appropriately determined in consideration of coating properties, film thickness, etc. For example, the solid content concentration may be 1 mass % or more, further 1.5 mass % or more, 2 mass % or more, etc. Also, it may be 90 mass % or less, further 80 mass % or less, 70 mass % or less, etc.

[0055] (Small particles) As described above, the curable composition may contain small-diameter particles having a particle diameter smaller than that of the convex-forming particles 18. The small-diameter particles may be added for purposes other than forming convex portions on the surface of the antiglare layer 16, such as imparting internal scattering to the antiglare layer 16 or adjusting the refractive index to a high level. The small-diameter particles may be inorganic particles or organic particles, or may contain both. The particle diameter of the small-diameter particles is preferably 200 nm or less, more preferably 120 nm or less, and even more preferably 100 nm or less, so as not to excessively increase the antiglare properties of the antiglare layer 16.

[0056] Glare can be reduced by appropriately increasing the internal scattering of the antiglare layer 16. The refractive index of the small diameter particles that impart internal scattering depends on the relationship with the refractive index of the entire antiglare layer 16, but is preferably 1.40 or more and 1.80 or less.

[0057] Furthermore, by making the antiglare layer 16 have a high refractive index, the antireflection function can be further improved when the low refractive index layer 14 is laminated thereon. A high refractive index refers to a state in which the refractive index at a measurement wavelength of 589.3 nm is 1.50 or more. The refractive index of the antiglare layer 16 is preferably 1.55 or more, and more preferably 1.60 or more. It is also preferably 1.80 or less, and more preferably 1.70 or less.

[0058] Examples of small-diameter particles (high-refractive index particles) made of inorganic particles that can be optically adjusted to a high refractive index include metal oxide particles made of oxides of metals such as titanium, zirconium, tin, zinc, silicon, niobium, aluminum, chromium, magnesium, germanium, gallium, antimony, and platinum. These may be used alone or in combination of two or more types as optically adjustable inorganic particles. Among these, titanium oxide and zirconium oxide are particularly preferred from the viewpoint of achieving both a high refractive index and transparency.

[0059] Examples of small-diameter particles (high-refractive index particles) made of resin particles that can be optically adjusted to a high refractive index include resin particles made of resins such as (meth)acrylic resin, styrene resin, styrene-(meth)acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenolic resin, polyethylene resin, cellulose, etc. These may be used alone as resin particles, or two or more types may be used in combination.

[0060] (Method of forming antiglare layer) The antiglare layer 16 can be formed on the surface of the base film 12 by applying a composition to become the antiglare layer 16 onto the surface of the base film 12, drying it as necessary, and then curing it by exposure to ionizing radiation. In this case, in order to improve the adhesion between the base film 12 and the antiglare layer 16, the surface of the base film 12 may be subjected to a surface treatment before coating. Examples of the surface treatment include corona treatment, plasma treatment, hot air treatment, ozone treatment, and ultraviolet treatment.

[0061] The composition that forms the antiglare layer 16 can be applied by various coating methods, such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, and kiss coating, or various printing methods, such as inkjet printing, offset printing, screen printing, and flexographic printing.

[0062] The conditions for the drying step are not particularly limited as long as the solvent contained in the coating liquid can be removed, but it is preferable to perform the drying step at a temperature of 50°C or higher and 150°C or lower for about 10 to 180 seconds. In particular, the drying temperature is preferably in the range of 50°C or higher and 120°C or lower. Furthermore, the surface roughness of the antiglare layer 16 varies depending on the drying temperature and time. For this reason, in the drying step, the drying temperature should be kept as constant as possible, and it is preferable that the temperature change from the specified temperature is 10°C or less both above and below. The temperature change is more preferably 5°C or less, and even more preferably 3°C or less.

[0063] For the irradiation of ionizing radiation, a high-pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ionizing radiation irradiation device can be used. The irradiation of ionizing radiation may be carried out under an inert gas atmosphere such as nitrogen, if necessary. The amount of ionizing radiation irradiation is not particularly limited, but is preferably 50 to 800 mJ / cm. 2 is preferable, and 100 to 300 mJ / cm 2 is more preferred.

[0064] When forming the antiglare layer 16, it is preferable that the density of extracted convex portions on the surface of the antiglare layer 16 to be formed is 10 / mm or more and 38 / mm or less. Then, the antiglare antireflection film 10 finally obtained after laminating the low refractive index layer 14 has an extracted convex portion density of 3 / mm or more and 30 / mm or less on the surface, and is likely to have excellent antiglare and antireflection properties. The extracted convex portion density on the surface of the antiglare layer 16 can be adjusted mainly by at least one parameter of the material, particle size, and content of the convex portion-forming particles 18 contained in the composition used to form the antiglare layer 16, the type and content of the binder resin and other components, and the film thickness to which the composition is applied. Furthermore, the extracted convex portion density on the surface of the antiglare layer 16 can also be adjusted by the conditions when the composition is applied and when the coating film is dried and cured.

[0065] <Low refractive index layer> The low refractive index layer 14 can enhance the antireflection properties of the antiglare antireflection film 10 by being formed on the antiglare layer 16. The low refractive index layer 14 is not particularly limited in configuration as long as it can enhance the antireflection properties of the antiglare antireflection film 10 by being disposed on the surface of the antiglare layer 16, but is preferably a layer in which hollow silica particles 22 are dispersed in a binder resin. The low refractive index layer 14 preferably further contains a fluorine-containing compound.

[0066] The thickness of the low refractive index layer 14 is preferably 60 nm or more and 160 nm or less. The wavelength (maximum absorption wavelength) at which the reflectance is minimized when the reflected light generated on the surface of the low refractive index layer 14 and the reflected light activated at the interface between the low refractive index layer 14 and the antiglare layer 16 cancel each other out is present at a longer wavelength as the thickness of the low refractive index layer 14 is thicker. However, if the thickness of the low refractive index layer is in the range of 60 nm or more and 160 nm or less, it is easy to position the maximum absorption wavelength in the visible range. Then, a well-reduced luminous reflectance can be obtained, and the reflection of light can be effectively reduced. From the viewpoint of setting the maximum absorption wavelength in the visible range without fail, avoiding the ultraviolet range, the thickness of the low refractive index layer 14 is more preferably 70 nm or more, and even more preferably 80 nm or more. Furthermore, if the thickness of the low refractive index layer 14 is set to 160 nm or less, the reflection effect against visible light can be enhanced as described above, and the unevenness provided by the convexity-forming particles 18 in the antiglare layer 16 can be well maintained on the surface of the low refractive index layer 14. From the viewpoint of further enhancing these effects, the film thickness of the low refractive index layer 14 is more preferably 140 nm or less, and further preferably 120 nm or less.

[0067] (binder resin) As the binder resin, a cured product of a thermosetting compound or a cured product of an ionizing radiation curable compound is preferred from the viewpoint of improving the scratch resistance of the low refractive index layer 14. Moreover, a cured product of an ionizing radiation curable compound is more preferred from the viewpoint of productivity.

[0068] Examples of the ionizing radiation curable compound include monomers, oligomers, prepolymers, etc. having a reactive group reactive to ionizing radiation. Examples of the reactive group reactive to ionizing radiation include radical polymerization type reactive groups having an ethylenically unsaturated bond such as acryloyl group, methacryloyl group, allyl group, vinyl group, etc., and cationic polymerization type reactive groups such as oxetanyl group. Among these, acryloyl group, methacryloyl group, and oxetanyl group are more preferred, and acryloyl group and methacryloyl group are particularly preferred. That is, (meth)acrylate is particularly preferred as the ionizing radiation curable compound.

[0069] Examples of the (meth)acrylate include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, and aryl (meth)acrylate. The (meth)acrylate may be composed of only a monofunctional (meth)acrylate, may be composed of a polyfunctional (meth)acrylate, or may be composed of a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. It is more preferable that the (meth)acrylate contains a polyfunctional (meth)acrylate. The ionizing radiation curable resin may be composed of one type of (meth)acrylate alone, such as those listed below, or may be composed of two or more types.

[0070] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, di Cyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate,Examples of the methacrylate include ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.

[0071] Examples of the polyfunctional (meth)acrylate include a bifunctional (meth)acrylate, a trifunctional (meth)acrylate, a tetrafunctional (meth)acrylate, etc. More specifically, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc. pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate.

[0072] The curable composition forming the low refractive index layer 14 may or may not contain a non-ionizing radiation curable resin in addition to the ionizing radiation curable resin. The curable composition forming the low refractive index layer 14 may also contain a photopolymerization initiator. If necessary, additives that are generally added to curable compositions may also be contained. Examples of such additives include dispersants, leveling agents, defoamers, thixotropic agents, antifouling agents, antibacterial agents, flame retardants, and slip agents. If necessary, a solvent may also be contained.

[0073] Examples of the non-ionizing radiation curable resin that can be contained in the curable composition that forms the low refractive index layer 14 include thermoplastic resins and thermosetting resins. Examples of the thermoplastic resins include polyester resins, polyether resins, polyolefin resins, polyamide resins, etc. Examples of the thermosetting resins include unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc.

[0074] Examples of the photopolymerization initiator include alkylphenone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2'-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and the like. Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more. The content of the photopolymerization initiator is preferably 0.1% by mass or more, more preferably 1% by mass or more, based on the total solid content of the curable composition. On the other hand, the content is preferably 10% by mass or less, more preferably 5% by mass or less.

[0075] Examples of the solvent used in the composition for forming the low refractive index layer 14 include alcohol-based solvents such as ethylene glycol monomethyl ether (EGM), propylene glycol monomethyl ether (PGM), and diethylene glycol monobutyl ether, ketone-based solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, and acetone, aromatic solvents such as toluene and xylene, and amide-based solvents such as N-methylpyrrolidone, acetamide, and dimethylformamide. These solvents may be used alone or in combination of two or more.

[0076] (Hollow Silica Particles) The hollow silica particles 22 are particles having a cavity inside the particle, and particularly refer to particles in which the ratio of the cavity is 5% or more of the volume. The hollow refers to a core-shell structure consisting of an outer shell and a cavity inside it, or a porous structure having a large number of cavities. The hollow silica particles 22 have a hollow structure, which can lower the refractive index of the low refractive index layer 14 and reduce light reflection. The hollow silica particles 22 are particles having an average particle diameter smaller than the average thickness of the low refractive index layer 14, and do not substantially contribute to the formation of the surface unevenness of the low refractive index layer 14. The hollow silica particles 22 are preferably particles having an average particle diameter smaller than the convexity forming particles 18 that form convexities on the surface of the antiglare layer 16. The shape of the hollow silica particles 22 is not particularly limited, but is preferably spherical, spindle-shaped, egg-shaped, flat, cubic, amorphous, etc. Among these, spherical, flat, cubic, etc. are particularly preferable.

[0077] In the hollow silica particles 22, the proportion of cavities is preferably 10% or more of the volume (the entire volume occupied by the hollow silica particles 22). When the proportion of cavities is 10% or more of the volume, the refractive index is lowered and light reflection is easily reduced. From the viewpoint of further enhancing this effect, the proportion of cavities is more preferably 20% or more of the volume, and further preferably 30% of the volume. On the other hand, the proportion of cavities is preferably 80% or less of the volume. When the proportion of cavities is 80% or less of the volume, a decrease in dispersibility of the hollow silica particles 22 can be suppressed. From the viewpoint of further enhancing this effect, the proportion of cavities is more preferably 60% or less of the volume.

[0078] The average particle diameter of the hollow silica particles 22 depends on the average film thickness of the low refractive index layer 14, but is preferably 5 nm or more, more preferably 20 nm or more, or 40 nm or more. Also, it is preferably 100 nm or less, more preferably 80 nm or less, or 70 nm or less. When the average particle diameter of the hollow silica particles 22 is within these preferred ranges, the low refractive index layer 14 can obtain excellent antireflection effect and transparency. The average particle diameter can be expressed as a volume-based average arithmetic value obtained by a laser diffraction / scattering method according to JIS Z8825. When the hollow particles 22 form an aggregate, the above average particle diameter applies not only to the primary particle diameter but also to the secondary particle diameter, which is an aggregate of particles.

[0079] The refractive index of the hollow silica particles 22 is preferably 1.01 or more, and more preferably 1.15 or more. Also, it is preferably 1.45 or less, and more preferably 1.38 or less, and even more preferably 1.35 or less. When the refractive index of the hollow particles 22 is within this range, an excellent antireflection effect can be obtained in the low refractive index layer 14.

[0080] The content of the hollow silica particles 22 in the low refractive index layer 14 is preferably 6.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 14. Then, excellent antireflection properties can be obtained in the low refractive index layer 14. From the viewpoint of further enhancing the effect, the content of the hollow silica particles 22 is more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 14. On the other hand, the content of the hollow silica particles 22 in the low refractive index layer 14 is preferably 49.9% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 14. Then, the deterioration of the scratch resistance of the low refractive index layer 14 is suppressed. From the viewpoint of further enhancing the effect, the content of the hollow silica particles 22 is more preferably 45% by mass or less, further preferably 40% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 14.

[0081] (Fluorine-containing compounds) The fluorine-containing compound can function as an antifouling agent in the low refractive index layer 14. In addition, the fluorine-containing compound can improve the slipperiness of the surface of the low refractive index layer 14, which can contribute to improving the scratch resistance. Examples of the fluorine-containing compound include (meth)acrylates containing a perfluoroalkyl group. Examples of such compounds include "KY-1203" manufactured by Shin-Etsu Chemical Co., Ltd., "Megafac RS-75" manufactured by DIC, "Optool DAC-HP" manufactured by Daikin Industries, Ltd., and "Ftergent 601AD" manufactured by Neos Co., Ltd. Such fluorine-containing compounds can suppress adhesion of dirt and fingerprints and facilitate removal of dirt and fingerprints. When the fluorine-containing compound is an ionizing radiation curable compound such as a (meth)acrylate containing a perfluoroalkyl group, the fluorine-containing compound can be cured by irradiation with ionizing radiation in the low refractive index layer 14 to form a copolymer with the ionizing radiation curable compound as the binder resin.

[0082] The content of the fluorine-containing compound in the low refractive index layer 14 is preferably 1.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 14. Then, the effect of improving the slipperiness and scratch resistance of the surface of the low refractive index layer 14 is highly obtained. In addition, the antifouling property is also improved. From the viewpoint of further enhancing these effects, the content of the fluorine-containing compound is more preferably 2.0% by mass or more, and even more preferably 3.0% by mass or more, relative to 100% by mass of the solid content of the low refractive index layer 14. On the other hand, the content of the fluorine-containing compound in the low refractive index layer 14 is preferably 15.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 14. Then, the deterioration of the scratch resistance in the low refractive index layer 14 is suppressed. From the viewpoint of further enhancing the effect, the content of the fluorine-containing compound is more preferably 13.0% by mass or less, even more preferably 10.0% by mass or less, and particularly preferably 5.0% by mass or less, relative to 100% by mass of the solid content of the low refractive index layer 14.

[0083] (Other forms of low refractive index layer) In the above, an embodiment has been described in which the low refractive index layer 14 is provided with an anti-reflection function on the surface of the anti-glare anti-reflection film 10 by using a cured film having a refractive index in a desired range by incorporating hollow silica particles in a binder resin. The low refractive index layer 14 may be configured as a multi-layer low refractive index layer formed by laminating two or more layers whose film thickness and refractive index are controlled. The multi-layer low refractive index layer exhibits an anti-reflection function by canceling out the inverted phases of incident light and reflected light by utilizing the interference effect of light. The wavelength region of visible light that exhibits the anti-reflection function may be, for example, 380 to 780 nm. The wavelength region with particularly high luminosity is the range of 450 to 650 nm, and it is preferable to design the low refractive index layer 14 so as to minimize the reflectance at 550 nm, which is the central wavelength of the low refractive index layer. In the multi-layer low refractive index layer, the degree of freedom in the optical design of the low refractive index layer 14 is increased by forming multiple layers of components with different refractive indices at a predetermined thickness, and the anti-reflection effect can be further improved. It is also possible to make the spectral reflectance characteristics closer to uniform (flat) across the visible light range.

[0084] The multi-layer low refractive index layer may be formed by sequentially laminating oxide layers having different refractive indices. For example, a two-layer structure may be used in which a silicon oxide layer having a low refractive index is laminated on a titanium oxide layer or zirconia oxide layer having a high refractive index. More preferably, a four-layer structure may be used in which a titanium oxide layer, a silicon oxide layer, a titanium oxide layer, and a silicon oxide layer are laminated in this order from the bottom, or a five-layer structure may be used in which a silicon oxide layer, a niobium oxide layer, a silicon oxide layer, a niobium oxide layer, and a silicon oxide layer are laminated in this order from the bottom. By forming such a two-layer low refractive index layer, four-layer low refractive index layer, or five-layer low refractive index layer, it is possible to reduce reflection in the wavelength region of visible light (for example, in the range of 380 to 780 nm) with high uniformity.

[0085] (Method of forming low refractive index layer) The low refractive index layer 14 can be formed by forming the antiglare layer 16 on the surface of the base film 12, and then coating a composition that will become the low refractive index layer 14. For example, a wet coating method or the like can be used for coating the low refractive index layer 14. As the wet coating method, for example, various coating methods such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, and kiss coating, and various printing methods such as inkjet printing, offset printing, screen printing, and flexographic printing can be used.

[0086] The low refractive index layer 14 can be formed by applying a composition that will become the low refractive index layer 14 onto the surface of the antiglare layer 16, drying it as necessary, and then curing it by irradiation with ionizing radiation to form the low refractive index layer 14 on the surface of the antiglare layer 16. In this case, in order to improve the adhesion between the antiglare layer 16 and the low refractive index layer 14, the surface of the base film 12 may be subjected to a surface treatment before coating. Examples of the surface treatment include corona treatment, plasma treatment, hot air treatment, ozone treatment, and ultraviolet treatment.

[0087] The conditions for the drying step are not particularly limited as long as the solvent used in the coating liquid can be removed, but it is preferable to perform the drying step at a temperature of 50° C. to 150° C. for about 10 to 180 seconds. In particular, the drying temperature is preferably in the range of 50° C. to 120° C.

[0088] For the irradiation of ionizing radiation, a high-pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ionizing radiation irradiation device can be used. The irradiation of ionizing radiation may be carried out under an inert gas atmosphere such as nitrogen, if necessary. The amount of ionizing radiation irradiation is not particularly limited, but is preferably 50 to 800 mJ / cm. 2 is preferable, and 100 to 300 mJ / cm 2 is more preferred.

[0089] When forming the low refractive index layer 14 as a multi-layer low refractive index layer having a structure in which two or more layers are laminated, as mentioned above as another form of low refractive index layer, each layer is required to have a high thickness accuracy, so that it is preferable to use a dry coating method for forming each layer. Examples of the dry coating method include PVD (Physical Vapor Deposition) methods such as vacuum deposition, reactive deposition, ion beam assisted deposition, sputtering, and ion plating, and CVD (Chemical Vapor Deposition) methods. Among these, the sputtering method is preferably used.

[0090] In the antiglare and antireflection film 10 described above, the density of extracted convex portions on the surface of the low refractive index layer 14 is 3 / mm or more and 30 / mm or less. As a result, the antiglare and antireflection film 10 suppresses glare, has good antiglare properties and black density in black display areas, and has excellent antireflection performance.

[0091] The antiglare antireflection film according to the present invention is not limited to the configuration of the antiglare antireflection film 10 according to the first embodiment described above. Other embodiments of the antiglare antireflection film according to the present invention will be described below.

[0092] [Anti-glare and anti-reflection film according to the second embodiment] 2 shows an antiglare antireflection film 20 according to a second embodiment of the present invention. The antiglare antireflection film 20 according to the second embodiment has a base film 12, a low refractive index layer 14 formed on one surface of the base film 12, and an antiglare layer 16 formed between the base film 12 and the low refractive index layer 14. The antiglare antireflection film 20 also has a transparent adhesive layer 24 on the other surface of the base film 12. A release film 26 is disposed on the surface of the transparent adhesive layer 24 as necessary. The release film 26 functions as a protective layer for the transparent adhesive layer 24 before use, and is peeled off from the transparent adhesive layer 24 when in use.

[0093] The antiglare antireflection film 20 of the second embodiment differs from the antiglare antireflection film 10 of the first embodiment in that it has a transparent adhesive layer 24 on the other side of the base film 12, but is otherwise similar to the antiglare antireflection film 10 of the first embodiment, and a description of the similar configuration will be omitted.

[0094] The transparent adhesive layer 24 is for attaching the antiglare antireflection film 20 to the surface of an image display device such as a touch panel with good adhesion. Furthermore, the antiglare antireflection film 20 has the effect of preventing the glass of an image display device such as a touch panel from shattering by having the transparent adhesive layer 24. That is, the antiglare antireflection film 20 also functions as a shatterproof film.

[0095] The adhesive composition forming the transparent adhesive layer 24 may contain a known adhesive resin such as an acrylic adhesive, a silicone adhesive, or a urethane adhesive. Among them, an acrylic adhesive is preferred from the viewpoint of optical transparency and heat resistance. The adhesive composition preferably further contains a crosslinking agent to increase the cohesive force of the transparent adhesive layer 24. The acrylic adhesive is preferably formed from an adhesive composition containing a (meth)acrylic polymer and a crosslinking agent.

[0096] The (meth)acrylic polymer is a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include an alkyl group-containing (meth)acrylic monomer, a carboxyl group-containing (meth)acrylic monomer, and a hydroxyl group-containing (meth)acrylic monomer.

[0097] Examples of the alkyl group-containing (meth)acrylic monomer include (meth)acrylic monomers having an alkyl group having 2 to 30 carbon atoms. The alkyl group having 2 to 30 carbon atoms may be linear, branched, or cyclic. More specific examples of the alkyl group-containing (meth)acrylic monomer include isostearyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, decyl (meth)acrylate, isononyl (meth)acrylate, nonyl (meth)acrylate, isooctyl (meth)acrylate, octyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, propyl (meth)acrylate, ethyl (meth)acrylate, and methyl (meth)acrylate.

[0098] Examples of the carboxyl group-containing (meth)acrylic monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, etc. The carboxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0099] Examples of hydroxyl group-containing (meth)acrylic monomers include hydroxylauryl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, etc. The hydroxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0100] The (meth)acrylic monomer forming the (meth)acrylic polymer may be any one of the above or a combination of two or more thereof.

[0101] Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, a metal chelate-based crosslinking agent, a metal alkoxide-based crosslinking agent, a carbodiimide-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, etc. The crosslinking agent may be used alone or in combination of two or more.

[0102] The adhesive composition may contain other additives in addition to the (meth)acrylic polymer and the crosslinking agent. Examples of other additives include crosslinking accelerators, crosslinking retarders, tackifier resins, antistatic agents, silane coupling agents, plasticizers, peeling aids, pigments, dyes, wetting agents, thickeners, ionizing radiation absorbers, preservatives, antioxidants, metal deactivators, alkylating agents, and flame retardants. From the viewpoint of productivity, the adhesive composition may be diluted using an organic solvent. These are appropriately selected and used depending on the application and purpose of the adhesive.

[0103] The thickness of the transparent adhesive layer 24 is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, and 100 μm or less, and even more preferably 50 μm or less. From the viewpoint of the shatterproof effect of glass, the transparent adhesive layer 24 preferably has an adhesive strength to glass of 4 N / 25 mm or more, more preferably 6 N / 25 mm or more, and even more preferably 10 N / 25 mm or more.

[0104] Methods for forming the transparent adhesive layer 24 on the other side of the base film 12 include a method in which an adhesive composition is directly applied onto the other side of the base film 12 to form the transparent adhesive layer 24, a method in which an adhesive composition is applied onto the surface of a release film 26 to form the transparent adhesive layer 24, and then transferred to the other side of the base film 12, and a method in which an adhesive composition is applied onto the surface of a first release film to form the transparent adhesive layer 24, and then a second release film is attached, and one of the release films is peeled off and transferred to the other side of the base film 12.

[0105] [Anti-glare and anti-reflection film according to the third embodiment] 3 shows an antiglare antireflection film 30 according to a third embodiment. The antiglare antireflection film 30 according to the third embodiment has a base film 12, a low refractive index layer 14 formed on one surface of the base film 12, an antiglare layer 16 formed between the base film 12 and the low refractive index layer 14, and a protective film 32 arranged on the surface of the low refractive index layer 14 via an adhesive layer 28. In addition, a transparent adhesive layer 24 is arranged on the other surface of the base film 12. A release film 26 is arranged on the surface of the transparent adhesive layer 24 as necessary.

[0106] The antiglare antireflection film 30 of the third embodiment differs from the antiglare antireflection film 20 of the second embodiment in that it has a protective film 32 on the surface of the low refractive index layer 14 via an adhesive layer 28; otherwise, it is similar to the antiglare antireflection film 20 of the second embodiment, and a description of the similar configuration will be omitted.

[0107] The protective film 32 can prevent the surface of the low refractive index layer 14 from being scratched during handling of the antiglare antireflection film 30, for example, when the antiglare antireflection film 30 is continuously processed by a roll process or the like, or when the antiglare antireflection film 30 is attached to an object such as a touch panel. The protective film 32 is attached to the surface of the low refractive index layer 14 via the adhesive layer 28. After processing or attaching the antiglare antireflection film 30, the protective film 32 is peeled off from the surface of the low refractive index layer 14 together with the adhesive layer 28. For this reason, in the adhesive layer 28, the adhesive force between the protective film 32 and the adhesive layer 28 is stronger than the adhesive force between the low refractive index layer 14 and the adhesive layer 28, and the adhesive force is adjusted to allow interfacial peeling between the low refractive index layer 14 and the adhesive layer 28. In the antiglare antireflection film 30 according to this embodiment, the density of extracted convex portions on the surface is specified for a state in which the protective film 32 and the adhesive layer 28 are peeled off to expose the low refractive index layer 14. That is, on the surface of the low refractive index layer 14 from which the protective film 32 and the adhesive layer 28 are peeled off, the density of extracted convex portions is 3 convex portions / mm or more and 30 convex portions / mm or less.

[0108] The material constituting the protective film 32 can be appropriately selected from those exemplified as the material constituting the base film 12. The thickness of the protective film 32 is not particularly limited, but can be within a range of 2 μm or more and 500 μm or less, or further 200 μm or less.

[0109] The adhesive forming the adhesive layer 28 is not particularly limited, and can be suitably formed from the same adhesive as the transparent adhesive layer 24 in the second embodiment. Specifically, the adhesive layer 28 can be suitably formed from an acrylic adhesive, a silicone adhesive, a urethane adhesive, or the like. In particular, an acrylic adhesive is suitable because of its excellent transparency and heat resistance. The acrylic adhesive is preferably formed from an adhesive composition containing a (meth)acrylic polymer and a crosslinking agent.

[0110] The (meth)acrylic polymer is a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include an alkyl group-containing (meth)acrylic monomer, a carboxyl group-containing (meth)acrylic monomer, and a hydroxyl group-containing (meth)acrylic monomer.

[0111] Examples of the alkyl group-containing (meth)acrylic monomer include (meth)acrylic monomers having an alkyl group having 2 to 30 carbon atoms. The alkyl group having 2 to 30 carbon atoms may be linear, branched, or cyclic. More specific examples of the alkyl group-containing (meth)acrylic monomer include isostearyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, decyl (meth)acrylate, isononyl (meth)acrylate, nonyl (meth)acrylate, isooctyl (meth)acrylate, octyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, propyl (meth)acrylate, ethyl (meth)acrylate, and methyl (meth)acrylate.

[0112] Examples of the carboxyl group-containing (meth)acrylic monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, etc. The carboxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0113] Examples of hydroxyl group-containing (meth)acrylic monomers include hydroxylauryl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, etc. The hydroxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0114] The (meth)acrylic monomer forming the (meth)acrylic polymer may be any one of the above or a combination of two or more thereof.

[0115] Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, a metal chelate-based crosslinking agent, a metal alkoxide-based crosslinking agent, a carbodiimide-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, etc. The crosslinking agent may be used alone or in combination of two or more.

[0116] The adhesive composition may contain other additives in addition to the (meth)acrylic polymer and the crosslinking agent. Examples of other additives include crosslinking accelerators, crosslinking retarders, tackifiers, antistatic agents, silane coupling agents, plasticizers, peeling aids, pigments, dyes, wetting agents, thickeners, ionizing radiation absorbers, preservatives, antioxidants, metal deactivators, alkylating agents, and flame retardants. These are appropriately selected and used depending on the application and purpose of the adhesive.

[0117] The thickness of the adhesive layer 28 is not particularly limited, but is preferably 1 μm or more, more preferably 2 μm or more, and more preferably 10 μm or less, more preferably 7 μm or less.

[0118] [Evaluation method for anti-glare and anti-reflection films] Next, a method for evaluating the antiglare and antireflection film according to an embodiment of the present invention will be described.

[0119] In the evaluation method of the antiglare antireflection film according to the present embodiment, the quality of the antiglare antireflection film is evaluated using the extracted convexity density as an index. As described above, the extracted convexity density is defined as the number of convexities having a height difference of 0.1 μm or more with respect to adjacent concaves in at least one direction in the extracted convexity / convexity distribution obtained by extracting components having a wavelength of 14 μm or more and 50 μm or less from the wavelength distribution obtained by Fourier transforming the unevenness distribution (cross-sectional profile) obtained by a laser microscope on an arbitrary straight line, and then performing an inverse Fourier transform. In other words, when the unevenness having a wavelength of 14 to 50 μm is extracted by a bandpass filter at an arbitrary point 1 mm in the cross-sectional profile, the number of convexities having a peak having a height difference of 0.1 μm or more with respect to at least one adjacent concave is the extracted convexity density.

[0120] As described above in detail about the anti-glare anti-reflection film 10 according to the first embodiment, when the density of the extracted convex portions is equal to or higher than a predetermined lower limit on the surface of the anti-glare anti-reflection film 10, good anti-glare properties are easily obtained. On the other hand, when the density of the extracted convex portions is suppressed to equal to or lower than a predetermined upper limit, a good low reflectance is obtained, and the anti-glare anti-reflection film is likely to have a good black color in the black display portion. Therefore, for any anti-glare anti-reflection film, when the surface has an extracted convex portion density within a range determined by the predetermined upper and lower limits, the anti-glare anti-reflection film can be determined to be a good product. A good product refers to an anti-glare anti-reflection film that has both the desired anti-glare properties and anti-reflection performance. It is sufficient to determine the lower limit of the extracted convex portion density according to the anti-glare properties that can be considered as good, and the upper limit of the extracted convex portion density according to the anti-reflection performance that can be considered as good.

[0121] For example, in any antiglare antireflection film, if the density of extracted convex portions on the surface is 3 / mm or more and 30 / mm or less, the antiglare antireflection film can be evaluated as a good product. The density of extracted convex portions is more preferably 5 / mm or more, and even more preferably 6 / mm or more. The density of extracted convex portions is more preferably 25 / mm or less, and even more preferably 15 / mm or less.

[0122] The anti-glare anti-reflection film to be evaluated by the method for evaluating the anti-glare anti-reflection film according to the present embodiment is not particularly limited as long as it has an uneven structure on the surface, but an anti-glare anti-reflection film including a structure in which a low refractive index layer 14 is laminated on the surface of an anti-glare layer 16, such as the anti-glare anti-reflection films 10, 20, and 30 according to the first, second, and third embodiments, can be exemplified as a suitable evaluation target. When layers that are peeled off during use are provided on the surface of the anti-glare anti-reflection film, the evaluation is performed in a state in which the layers are peeled off. For example, when layers that are peeled off during use are provided on the surface of the low refractive index layer 14, such as the protective film 32 and the adhesive layer 28 of the anti-glare anti-reflection film 30 according to the third embodiment, the evaluation is performed in a state in which the layers are peeled off and the low refractive index layer 14 is exposed.

[0123] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, in the above embodiment, it is described that the surface of the base film 12 may be subjected to a surface treatment, but instead of the surface treatment, an easy-adhesion layer may be provided on the surface of the base film 12. In addition, various functional layers such as a gas barrier improving layer, an antistatic layer, and an oligomer block layer may be provided on the surface of the base film 12 before each layer is formed. Furthermore, as shown in FIG. 3, the protective film 32 is shown as being added to the antiglare antireflection film 20 of the second embodiment shown in FIG. 2, but it may be added to the antiglare antireflection film 10 of the first embodiment shown in FIG. 1. EXAMPLES

[0124] The present invention will be described in detail below with reference to examples and comparative examples. Unless otherwise specified, each step of preparing and evaluating a sample is carried out in air at room temperature.

[0125] <Preparation of composition for forming antiglare layer> Each component was mixed in the composition (mass %) shown in Table 1 to prepare a composition for forming an antiglare layer.

[0126] The materials used in the composition for forming the antiglare layer are as follows: Hereinafter, the particle size of each substance is expressed as the average particle size. <Binder resin> Binder resin composition 1: "Z-735-3L" manufactured by AICA Corporation; a composition containing (meth)acrylic resin, polymethyl methacrylate particles (particle diameter 80 nm), photopolymerization initiator, and solvent (methyl ethyl ketone (MEK), ethyl acetate); solid content concentration 50% by mass Binder resin composition 2: "Z-878-17HL" manufactured by AICA Corporation; a composition containing (meth)acrylic resin, silica particles (particle diameter 25 nm), photopolymerization initiator, and solvent (propylene glycol monomethyl ether (PGM)) - solid content concentration 50% by mass Binder resin composition 3: A mixture of Aica Kogyo's "Z-757-CL7" and Aica Kogyo's "Z-757-CL8" in a ratio of 80:20 (by mass) "Z-757-CL7": A composition containing a (meth)acrylic resin, silica particles (particle diameter 20 nm), a photopolymerization initiator, and a solvent (propylene glycol monomethyl ether); solid content concentration 40% by mass "Z-757-CL8": A composition containing a (meth)acrylic resin, a photopolymerization initiator, and a solvent (PGM); solid content concentration: 40% by mass <Particles for forming convex portions> Particles for forming unevenness 1: Sekisui Chemical's "Techpolymer SSX-105"; Polymethylmethacrylate (PMMA) particles; Particle diameter 5.5 μm ·Irregularity forming particles 2: "Techpolymer SSX-104" manufactured by Sekisui Plastics; PMMA particles; particle size 4.0 μm Particles for forming unevenness 3: Nissan Chemical's "Optbeads 3500M"; melamine silica composite particles; particle diameter 3.5 μm ·Irregularity forming particles 4: "Techpolymer SSX-103" manufactured by Sekisui Plastics; PMMA particles; particle size 3.1 μm Particles for roughening 5: Soken Chemical's "Chemisnow MX300"; PMMA particles; particle size 3.0 μm Particles for forming unevenness 6: AICA Kogyo's "Z-AGD-10"; silica particles; particle size 2.0 μm <Other ingredients> High refractive index particles 1: "Zircostar ZP-153" manufactured by Nippon Shokubai; contains zirconia particles (particle diameter 10 nm) and dispersion medium (MEK); solid content concentration 60% Leveling agent 1: Neos "Ftergent 602A"; contains ionizing radiation reactive fluorine-containing compound and solvent (ethyl acetate); solids concentration 50% by mass Leveling agent 2: Kyoeisha Chemical's "LE-604"; contains an ionizing radiation reactive fluorine-containing compound and a solvent (3-methoxy-3-methyl-1-butanol); solids concentration 30% by mass

[0127] <Preparation of Antiglare Layer> The antiglare layer-forming composition prepared above was applied to a substrate film (Toyobo PET film, "Cosmoshine TA-048", thickness 80 μm) using a wire bar so as to obtain a film thickness as shown in Table 1. After drying at 80°C for 60 seconds, the composition was irradiated with light of 80 mJ / cm using an electrodeless (microwave) lamp. 2 The film was irradiated with ultraviolet light of 1000 nm to form an antiglare layer.

[0128] <Preparation of composition for forming low refractive index layer> The following fluorine-containing compound was added in an amount of 4 parts by weight per 100 parts by weight of resin solids to the following hollow silica-containing ionizing radiation curable resin composition, and the mixture was diluted with methyl isobutyl ketone (MIBK) to give a solids concentration of 4 mass%, thereby preparing a composition for forming a low refractive index layer. Hollow silica-containing ionizing radiation curable resin composition: "Opstar TU2361" manufactured by Arakawa Chemical Industries; containing hollow silica particles, (meth)acrylic resin, fluorine-based resin, additives, photopolymerization initiator, and solvent; solid content concentration 10% by mass Fluorine-containing compound: Shin-Etsu Chemical Co., Ltd.'s "KY-1203"; (meth)acrylate containing perfluoroalkyl groups

[0129] <Preparation of anti-glare and anti-reflection film> The prepared composition for forming a low refractive index layer was applied onto the surface of the antiglare layer formed above using a wire bar #4. After drying at 80°C for 60 seconds, the composition was irradiated with a light intensity of 80 mJ / cm2 using an electrodeless (microwave type) lamp in a nitrogen atmosphere. 2 The film was irradiated with ultraviolet light of 1000 nm to form a low refractive index layer.

[0130] As described above, the antiglare and antireflection films of Examples 1 to 9 and Comparative Examples 1 to 3 were prepared.

[0131] <Evaluation method>

[0132] (1) Refractive index The refractive indexes of the antiglare layer and the low refractive index layer were evaluated using a microspectrophotometer (Otsuka Electronics' "OPTM-F1"), and the refractive index at a wavelength of 550 nm was calculated from the reflection spectrum in the wavelength range of 380 to 780 nm.

[0133] (2) Film thickness The thicknesses of the antiglare layer and the antireflection layer were measured by spectroscopic interference using a Filmetrics F20 film thickness measurement system.

[0134] (3) Evaluation using a laser microscope Using a 3D measuring laser microscope (Olympus "LEXT OLS5000"; laser wavelength 405 nm, objective lens magnification 10x, beam spot radius 0.2 μm), cross-sectional profiles were obtained in arbitrarily selected areas of 0.65 mm length on the surfaces of the anti-glare layer and the low refractive index layer.

[0135] The cross-sectional profile obtained was Fourier transformed to obtain the wavelength distribution, from which wavelength components between 14 μm and 50 μm were extracted, and further inverse Fourier transformed to obtain the unevenness extraction distribution. Specifically, a bandpass filter (FIR filter, Hanning window) was applied using the analysis function of graph creation software ("Igor Pro" manufactured by Wave Metrics) to obtain the wavelengths of 14 to 50 μm (wavenumbers of 0.02 to 0.07 μm). -1 ) and plotted on a graph to obtain the extracted unevenness distribution. In the obtained extracted unevenness distribution, the number of convexities whose height difference with at least one adjacent concave portion was 0.1 μm or more was counted, and the number of convexities per mm was converted to the extracted convexity density.

[0136] Additionally, the arithmetic average roughness Ra of the surfaces of the antiglare layer and the low refractive index layer was determined based on JIS B0601:2013 from the cross-sectional profile obtained by the 3D measuring laser microscope.

[0137] (4) Evaluation using a stylus-type surface roughness measuring device The arithmetic average roughness Ra of the surfaces of the anti-glare layer and the low refractive index layer was determined based on JIS B0601:2013 using a stylus-type surface roughness profiler (Tokyo Seimitsu's "Surfcom1500 SD2" with a stylus tip curvature radius of 1 μm).

[0138] (5) Haze (Hz) Using a haze meter (BYK-GARDNER's "Haze-gard plus"), the haze (Hz) was measured from the surface of the antiglare layer and the low refractive index layer. If the haze is 2.0% or more, the antiglare antireflection film can be considered to have high antiglare properties.

[0139] (6)Visual sensitivity reflectance (SCI) The surface of the anti-glare anti-reflection film opposite to the low refractive index layer was roughened with #400 sandpaper and painted with black paint. The 8° reflectance of the surface of the low refractive index layer was measured using an ultraviolet-visible near-infrared spectrophotometer (Shimadzu Corporation's "UV-3600") equipped with a dedicated integrating sphere attachment (Shimadzu Corporation's "ISR-3100A"). The measured value of the 8° reflectance obtained was multiplied by the relative luminous efficiency value to calculate the luminous efficiency reflectance in diffuse reflected light including regular reflected light (SCI: Speclar Component Include). If the luminous efficiency reflectance is 1.3% or less, the anti-glare anti-reflection film can be considered to have high anti-reflection performance.

[0140] (7) Glare The antiglare and antireflection film was placed with the low refractive index layer side facing up on the screen of an iPad (registered trademark) (3rd generation, screen resolution: 264 ppi) as a high-definition liquid crystal display, and the entire screen was colored green (R0, G255, B0 in the RGB color system), and glare was evaluated visually. The following ranks were given for the evaluation. ◎ No glare There is a slight glare, but it does not affect visibility. △ There is some glare, but it doesn't affect the practical use. × Glare is clearly visible

[0141] <Evaluation Results> Representatively, Figures 4 to 7 show the results of measurements using a laser microscope for Example 2 and Comparative Example 1. Figures 4 and 6 respectively show (a) a cross-sectional profile and (b) an extracted unevenness distribution obtained on the surface of the antiglare layer for the antiglare antireflection films of Example 2 and Comparative Example 1. Figures 5 and 7 respectively show (a) a cross-sectional profile and (b) an extracted unevenness distribution obtained on the surface of the low refractive index layer for the antiglare antireflection films of Example 2 and Comparative Example 1.

[0142] In all of Figures 4 to 7, components with wavelengths of 14 to 50 μm are extracted from the cross-sectional profile obtained by a laser microscope in (a) to obtain the extracted unevenness distribution in (b), which removes minute noise and large undulation components and emphasizes the unevenness structure formed by the particles for forming convexities. In each extracted unevenness distribution, convexities that have a height difference of 0.1 μm or more with adjacent concaves in at least one direction are indicated by a triangular mark (▽). The number of these convexities converted per 1 mm of length is the extracted convexity density.

[0143] In Example 2 and Comparative Example 1, when comparing the extracted unevenness distribution of the antiglare layer surface with the extracted unevenness distribution of the low refractive index layer surface, that is, comparing Figure 4(b) with Figure 5(b) and Figure 6(b) with Figure 7(b), the low refractive index layer surface has a smaller unevenness height difference and also has fewer convexities indicated by triangle marks. This shows that the formation of the low refractive index layer reduces the unevenness detected by the laser microscope.

[0144] Furthermore, when comparing the extracted unevenness distributions of the antiglare layer surface and the low refractive index layer surface between Example 2 and Comparative Example 1, that is, comparing Figures 4(b) and 6(b) and Figures 5(b) and 7(b), it is found that the unevenness height difference is smaller on the surfaces of both the antiglare layer and the low refractive index layer in Example 2, and the number of convex portions indicated by triangle marks is also smaller. This difference in unevenness distribution can be associated with the difference in the configuration of the antiglare layer, as will be explained next.

[0145] Table 1 below shows the structure of the antiglare layer and various evaluation results for the antiglare layer and the low refractive index layer for each of the antiglare and antireflection films of Examples 1 to 9 and Comparative Examples 1 to 3. Here, the evaluation results for the low refractive index layer were evaluated for the entire completed antiglare and antireflection film.

[0146] [Table 1]

[0147] In Examples 1 to 9, an antiglare antireflection film is formed by forming an antiglare layer and a low refractive index layer in this order on the surface of a substrate.Then, on the surface of the low refractive index layer of the antiglare antireflection film, the density of extracted convex parts is 3 pieces / mm or more and 30 pieces / mm or less.In correspondence with this, the antiglare antireflection film suppresses glare, has good antiglare properties, and has excellent antireflection performance.

[0148] In Comparative Example 1 and Comparative Example 2, the density of the extracted convex portions on the surface of the low refractive index layer is greater than 30 pieces / mm, and the antireflection properties are poor and glare is clearly noticeable. On the other hand, in Comparative Example 3, the density of the extracted convex portions on the surface of the low refractive index layer is less than 3 pieces / mm, and the haze is low. In other words, the antiglare properties are poor.

[0149] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and various modifications can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0150] 10. Anti-glare and anti-reflective film 12 Base film 14 Low refractive index layer 16 Anti-glare layer 24 Transparent adhesive layer 26 Release film 28 Adhesive layer 32 Protective film

Claims

1. A method for evaluating an anti-glare anti-reflection film, comprising: an anti-glare layer and a low refractive index layer formed in this order on a substrate film; extracting components having wavelengths of 14 μm or more and 50 μm or less from a wavelength distribution obtained by Fourier transforming an unevenness distribution obtained on an arbitrary straight line using a laser microscope; and then performing an inverse Fourier transform on the extracted unevenness distribution obtained; and evaluating the quality of the anti-glare anti-reflection film using, as an index, the extracted convexity density, which is defined as the number of convexities having a height difference of 0.1 μm or more between themselves and adjacent concaves in at least one direction.

2. 2. The method for evaluating an antiglare antireflection film according to claim 1, wherein the antiglare antireflection film is evaluated as being of good quality if the density of the extracted convex portions on the surface of the low refractive index layer is 3 / mm or more and 30 / mm or less.

3. 3. The method for evaluating an antiglare antireflection film according to claim 2, wherein in the antiglare antireflection film evaluated as a good product, the extracted convex portion density on the surface of the antiglare layer evaluated at the time the antiglare layer is formed is 10 pieces / mm or more and 38 pieces / mm or less.

4. 4. The method for evaluating an antiglare antireflection film according to claim 2 or 3, wherein the antiglare antireflection film evaluated as a non-defective product has an arithmetic mean roughness Ra, as measured by a stylus-type surface roughness measuring device on the surface of the low refractive index layer, of 0.015 μm or more and 0.06 μm or less, as defined in JIS B0601:2013.

5. 5. The method for evaluating an antiglare antireflection film according to claim 2, wherein the antiglare layer of the antiglare antireflection film is evaluated as a non-defective product, and the surface of the antiglare layer has an arithmetic mean roughness Ra, as measured by a stylus-type surface roughness measuring device, of 0.015 μm or more and 0.06 μm or less, as defined in JIS B0601:2013.

Citation Information

Patent Citations

  • Coating composition for forming low refractive-index layer, reflection-preventing film, polarizing plate, and liquid crystal display device

    JP2006257402A

  • Antiglare hard coat film, polarizing plate and image display apparatus using the same, method for evaluating the same and method for producing the same

    JP2009288655A

  • Hard-coated antiglare film, polarizing plate and image display including the same and method for manufacturing hard-coated antiglare film

    JP2010009007A

  • Anti-glare Anti-reflection film and image display including the same

    JP2010078698A

  • Antiglare film, polarizing plate, image display device, and method for manufacturing antiglare film

    JP2012159691A